VD_FINDINFO HC / 2010 / 724 vom 2. Dezember 2010 - VD Tribunal cantonal (2010)
BAIL À LOYER, TRANSACTION COUPLÉE, PORTE-FORT, MODIFICATION DE LA DEMANDE | 111 CO, 254 CO, 3 CPC, 452 al. 1ter CPC, 452 al. 2 CPC, 452 CPC, 60 CPC, 13 LTB, 5 al. 1 LTB, 5 al. 3 LTB, 5 LTB